Immunohistochemical evaluation of vascular endothelial growth factor and transforming growth factor-beta on osseointegration of CpTi implant radiated by low level laser therapy - Mayada K Jaafar; Eman I Al- Tamemi (College of Dentistry/ University of Baghdad, 2014)
Background: Dental implants provide a unique treatment modality for the replacement of lost dentition .This is accomplished by the insertion of relatively inert material (a biomaterial) into the soft and hard tissue of the jaws, there by providing support and retention for dental prostheses. Low level laser therapy (LLLT) is an effective tool used to prompt bone repair and modeling post surgery; this has referred to the biostimulation effect of LLLT. The aims of this study were to evaluate the immmunohistochemical expression of vascular endothelial growth factor (VEGF) and transforming growth factor -beta (TGF-β) in experimental and control groups with mechanical test. Materials and Methods: Thirty two adult New Zealand white rabbits used, screw titanium implants inserted in the tibia. The right side is considered as experimental groups and the left side considered as control groups. Low power diode laser (GaAlAs) with wave length (904nm) and (5mW) power applied with the right screw implants. The sample divided into four groups, eight rabbits are sacrificed at four interval 4days, 1 weeks, 2weeks, and 6weeks respectively. immunohistochemical (VEGF&TGF-β), were done for each interval with mechanical test in 2 and 6 weeks . Results: Immunohistochemical findings revealed high positive expression for VEGF and TGF-β in experimental implant in comparison to control one and the acceleration of bone formation and more rapid healing process in the screw implant with laser irradiation than in the control implant. Removal torque test showed dramatic increase with the presence of laser irradiation especially with advancing time. Conclusion: This study was illustrated that the LLLT applications enhance bone formation and increase osseointegration.